Macroeconomic management and building social consensus : an evaluation of the Barbados Protocols - Downes, Andrew S. (2004)
Evaluates the primary provisions in the four Barbados Protocols covering the period 1993 to 2004. Undertakes an evaluation of the economic and industrial relations provisions in the Protocol. Discovers that the results of the statistical data suggest that the Protocols have provided modest, but short-lived, economic gains and a useful mechanism for providing non-governmental parties with a 'voice' in public policy making.